The Characteristics of Working Overtime and Their Associations With Nurse and Patient Outcomes: A Systematic Review Protocol - Braiki, Raouaa; Rochefort, Christian (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Université de Montréal, 2025)
Introduction: Healthcare systems often use overtime to manage nursing shortage and to provide continuous and required nursing care. Studies have examined the impact of working overtime on both nurse and patient outcomes with conflicting results. Objectives: We aim to summarize existing evidence on the association between overtime work and nurse and patient outcomes; and to identify avenues for future research. Method: A systematic search of MEDLINE, CINAHL, PsycINFO, Scopus, Campbell, and Cochrane Library will be conducted to identify relevant studies on the association between overtime and nurse and patient outcomes. The period covered will be from April 2013 to May 2025. Two independent reviewers will perform screening, study selection, and data extraction. A qualitative synthesis of the available evidence will be performed. The results will be reported in tables. Discussion and Research Spin-offs: This systematic review will inform nursing research and practice and provide valuable recommendations that can be used to guide policies and managers’ decisions regarding working overtime in nursing settings.